2008
DOI: 10.1002/pssb.200743348
|View full text |Cite
|
Sign up to set email alerts
|

Differential surface photovoltage spectroscopy of δ‐doped GaAs/AlAs multiple quantum wells below and close to Mott transition

Abstract: Differential surface photovoltage (DSPV) spectra of Be δ‐doped GaAs/AlAs multiple quantum wells (MQWs) with doping densities below (5 × 1010 cm–2) and near (5 × 1012 cm–2) a Mott transition were studied at 300 K and 90 K. From the line shape analysis of the DSPV spectra, exhibiting obvious doping and temperature dependences, an origin of optical transitions has been revealed. The spectra of lightly doped structures were accounted for by ground state heavy and light‐hole related excitonic transitions. In highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…25 Application of modulation spectroscopy has allowed estimation of internal built-in electric fields and broadening mechanisms, 26 discrimination between the origin of optical transitions below and close to the Mott transition, and demonstration that with increasing doping level phase space filling effects dominate over the Coulomb screening. 27 Photoluminescence (PL) and time-resolved PL spectra studies have also demonstrated acceptor-impurity induced effects in the (PL) line shapes dependent on the QW widths 28 and allowed one to investigate possible mechanisms for the carrier radiative recombination, both above and below the Mott metal-insulator transition. 29 In this work, we complement this family of experimental techniques by showing that low-frequency noise measurements are useful method to extract a large variety of information investigating beryllium d-doped GaAs/AlAs QWs.…”
Section: Introductionmentioning
confidence: 99%
“…25 Application of modulation spectroscopy has allowed estimation of internal built-in electric fields and broadening mechanisms, 26 discrimination between the origin of optical transitions below and close to the Mott transition, and demonstration that with increasing doping level phase space filling effects dominate over the Coulomb screening. 27 Photoluminescence (PL) and time-resolved PL spectra studies have also demonstrated acceptor-impurity induced effects in the (PL) line shapes dependent on the QW widths 28 and allowed one to investigate possible mechanisms for the carrier radiative recombination, both above and below the Mott metal-insulator transition. 29 In this work, we complement this family of experimental techniques by showing that low-frequency noise measurements are useful method to extract a large variety of information investigating beryllium d-doped GaAs/AlAs QWs.…”
Section: Introductionmentioning
confidence: 99%